A case study in spatial-temporal accessibility for a transit system. (February 2019) - Handley, John C.; Fu, Lina; Tupper, Laura L.
Abstract: We show the impact on transit network connectivity of a major network redesign using a comprehensive connectivity measure. This measure captures the quality of service impact – the difference between the actual accessibility and the designed accessibility as a function of space and time. The former is influenced by on-time performance and ability to make transfers. The measure is unique in that it incorporates both spatial and temporal aspects of the transportation network, so that the effects of the network geometry, transportation services schedules, and operational performance (in the form of service reliability / schedule adherence) are all appropriately reflected in this unified measure. We employ a spatial statistical model to tie aggregate ridership to average connectivity across transportation analysis zones. The statistically significant relationship indicates that, at least in aggregate, connectivity and demand are linked. Using spatio-temporal clustering, we show where, when, and how accessibility is impacted by a significant network redesign.